COVID-19 pandemic in Bangladesh: A scoping review of governance issues affecting response in public sector - Syed Masud Ahmed; Mahruba Khanam; Noshin Sayiara Shuchi (Elsevier, 2024)
Background: On January 30, 2020, WHO declared COVID-19 as a Global Public Health Emergency. The first three COVID-19 cases in Bangladesh were confirmed on March 8, 2020. Thus, Bangladesh got substantial time to prepare the people and the health systems to respond to the outbreak However, neither the health ministry nor the government was found to rise to the occasion and provide the necessary stewardship for a coordinated and comprehensive response. Objective: The importance of governance to mount an evidence-based pandemic response cannot be overemphasised. This study presents critical reflections on the Bangladesh government's COVID-19 response through a review of selected papers, with expert deliberations on the review findings to consolidate emerging lessons for future pandemic preparedness. Study design: A scoping review approach was taken for this study. Methods: Documents focusing on COVID-19 governance were selected from a repository of peer-reviewed articles published by researchers using data from Bangladesh (n = 11). Results: Findings reveal Bangladesh's COVID-19 response to be delayed, slow, and ambiguous, reflecting poorly on its governance. Lack of governance capability in screening for COVID-19, instituting quarantine and lockdown measures in the early weeks, safety and security of frontline healthcare providers, timely and equitable COVID-19 testing, and logistics and procurement were phenomenal. The pandemic unmasked the weaknesses of the health system in this regard and "created new opportunities for corruption." The failure to harmonise coordination among the government's different agencies for the COVID-19 response, along with poor risk communication, which was not culture-sensitive and context-specific. Over time, the government initiated necessary actions to mitigate the pandemic's impact on the lives and livelihoods of the people. Diagnostic and case management services gained strength after some initial faltering; however, the stewardship functions were not seamless. Conclusions: Shortage of healthcare workers, incapability of health facilities to cater to COVID-19 suspects and cases, absence of health system resilience, and corruption in procurement and purchases were limited the government's COVID-19 response. These need urgent attention from policymakers to better prepare for the next epidemic/pandemic.